Biomarkers predicting postoperative adverse outcomes in children with congenital heart disease: a systematic review and meta-analysis - Zhou, Shifan; Liu, Lu; Jin, Xiaochuang; Dorikun, Daniel; Ma, Songfeng (Frontiers in Pediatrics, 2025)
ObjectiveTo statistically analyze biomarkers predicting postoperative outcomes in children with congenital heart disease (CHD).MethodsPubMed, Embase, Cochrane Library, and Web of Science were performed to search up to February 2024. The measured outcomes were biomarkers, mortality, length of hospital stay, complication rates, and infection rates. Adults with CHD were excluded. Standard deviation or odds ratio (OR) with 95% confidence interval (95% CI) were extracted. A random-effects model synthesized SMDs or ORs with 95% CIs. Sensitivity analysis investigated heterogeneity, and Egger's test assessed publication bias.ResultsSeventeen eligible articles were included, the biomarkers involved include serum lactate, NT-Pro BNP, PaO2, serum creatinine, C1-INH activity, ST2, serum chloride concentration, GH, glycemia, cTOI, NLR, serum albumin, and glucose levels, with 2,888 patients who underwent surgery(modified Norwood procedure, arterial switch procedure, biventricular repair etc.). Serum lactate was higher in the postoperative death group (SMD: 1.18, 95% CI: 0.59–1.77). Lower postoperative N-terminal pro-B-type natriuretic peptide (NT-pro BNP) levels were associated with lower mortality (OR: 0.23, 95% CI: 0.08–0.68) and shorter mechanical ventilation time (OR: 0.40, 95% CI: 0.18–0.90). Higher serum albumin levels were associated with longer hospital stays (OR: 3.12, 95% CI: 1.66–5.84). Significant heterogeneity was found in serum creatinine, B-type natriuretic peptide (BNP), serum lactate, and NT-Pro BNP. Publication bias was detected in some studies.ConclusionSerum lactate, NT-Pro BNP, and serum albumin are reliable biomarkers for predicting adverse outcomes in children with CHD after surgery.Systematic Review RegistrationPROSPERO [CRD42024512753].